Users' satisfaction in the use of abstracts and indexes on CD-ROM in selected academic libraries - Marzo, Arlene A.; David, Lourdes T.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1995)
This study determined the satisfaction of 323 users after searching the abstracts and indexes on CD-ROM of ten academic libraries: the Ateneo de Manila Rizal Library, the De La Salle University Library, the University of Santo Tomas Main Library, the U.P. Los Baños Main Library, the U.P. Manila University Library and the following University of the Philippines Diliman Libraries; Main Library, College of Education, College of Economics, Institute of Library Science and College of Science Libraries.
Using a questionnaire, it identified who are the users of abstracts and indexes on CD-ROM, the users' purposes for literature searching, the problems and difficulties encountered while searching and using the CD-ROM, the factors affecting their searching success and the favorable features of CD-ROM. Their preferences for the CD-ROM format was also determined and their reasons for such preference.
From the results of the survey, it was found out that majority of the users were students, majority of which came from the senior college level with an average age of 21, mostly female who had background in computers and had used the abstracts and indexes on CD-ROM before. Four top fields of major are engineering, biology, medicine and education. They became aware of its availability from the librarian. The main reasons for searching are: (1) writing a term paper, report or article; (2) conducting a survey; (3) preparing an assignment and (4) compiling a bibliography.
Most of the respondents are regular users (2-5 times) and forty percent use Boolean logic in searching. Majority of the students expressed preference for the CD-ROM format rather than the printed one for the following reasons: it saves time; faster retrieval and easier access. Most of the cited reasons for problems encountered are: they are not familiar how it works, it was confusing to use and the lack of training manuals. Some of the users noted that it was difficult for them to obtain good results because of its limited coverage, very general information and too many hits. Based on the responses to question on the relevancy of search results over the number of searches, the estimated average of useful searches were more than sixty percent.
Results indicate that familiarity with computers and knowledge in formulating search strategies affect the search performance of the user. Therefore, the assumption that the familiarity with computers and knowledge in formulating search strategy affect the users' success and satisfaction was accurate. Overall, the users were satisfied from their search results. Most of the remarks about their searching experience were favorable. Most of their retrieved citations were all current. Seventy-five percent indicated their agreement to use the abstracts and indexes on CD-ROM again. For additional comments and suggestions, a number of users suggested that the library should add more workstations to accommodate longer time of searching per user. Some had requested for newer versions of their computers as some of the CPU's they used were 286 and were rather slow. A number had wanted to had the full text of their cited materials available at their library.
It was recommended that instruction in CD-ROM searching should be a high priority to overcome most of the problems encountered. Other factors discussed and recommended aside from user education are networking, staff involvement and training, development of policies on the operating procedures that could serve as guidelines for the staff when attending to the needs of the users. Some of the implications that resulted from the study is the increase in user demands, the demand for document delivery and the use of more abstracts and indexes on CD-ROM as an alternative to online searching.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Indexes -- Use studies; Information services -- Use studies. -- Philippines -- Manila Metropolitan Area